Gender and mental health of adolescents: A conceptual framework developed in a Delphi study - Anita Alaze; John Grosser; Oliver Razum; Céline Miani (PLoS ONE, 2025)
Objective Adolescence is one of the most neglected developmental phases, yet there are few phases in the life course when gender socialisation is as intense. So far, no framework or theory exists that theoretically conceptualises gender norms, gender attitudes and mental health outcomes. To address this gap, we aim to develop a conceptual framework that illustrates the interplay of key constructs in the gendered pathways of health, using the Delphi technique. Methods We carried out a Delphi study enrolling an international panel of 21 experts from different disciplines, with 43% of the respondents completing all three survey rounds. We asked the experts to identify core constructs (first round), suggest operationalisations of the constructs (second round), and to hypothesise about their relationships (third round). Items were included, excluded or adapted according to experts’ feedback. A 70% threshold was used for consensus. Results The panelists consented on the following core constructs: gender norms (social environment), sex assigned at birth, gender attitudes, gender roles, competencies, and gender identity to the mental health of adolescents. They further consented on gender approaches, namely the intersectional, multidimensional and multilevel approach as well as the power relations lens. The operationalisation of the constructs in round two led to the inclusion of variables forming an intersectional lens and four social environment levels: the household, community, political and digital level. In round three, the experts formed 14 hypotheses about the relationships between the core constructs. Conclusion The derived conceptual framework links the interplay of six key constructs, four gender approaches and four social environment levels to adolescent mental health. Future research should validate and apply the hypothesised relationships between the constructs to disentangle the gendered pathways to (mental) health in adolescence.